Temporal Relationship between Action and Visual Outcome Modulates Brain Activation: An fMRI Study - MATSUZAWA, Masako; SUGIO, Takeshi; NAKAI, Toshiharu; KATO, Chikako; MATSUO, Kayako (Magnetic Resonance in Medical Sciences, 2005)
Monitoring the visual outcome of our actions is critical to our visuo-motor behavior. To investigate the neural basis of monitoring visual change produced by self-movement, we examined the temporal relationship between manual depression of a button and visual feedback on activation of the brain. Six neurologically normal subjects participated in 3 experiments (synchronous, delayed, and visual [control]). Magnetic resonance (MR) images of their brains were acquired during the experiments using a scanner operating at 3T. In the synchronous experiment, subjects pressed a button at self-paced intervals and received synchronous visual stimuli in response. In the delayed experiment, visual stimuli were presented with a delay after subjects pressed a button at self-paced intervals. In the control experiment (visual experiment), subjects did not press the button, but viewed visual stimuli generated by a computer at random intervals. In the synchronous experiment, activation in the cerebellum and right parietal lobe was stronger than in the delayed experiment, whereas activation in the primary visual cortex was weaker than in the delayed and visual experiments. These results suggest that visual outcomes produced synchronously with action are processed in the cerebellum and the parietal area for the organization of optimal motor behavior, rather than in the primary visual area that is known to process the visual properties of external objects. The cerebellar signal related to visuo-motor contingency may modulate the cortical processing of visual input that is synchronous with action.